Profile mathematikbezogener motivationaler Prädispositionen: Zusammenhänge zwischen Motivation, Interesse, Fähigkeitsselbstkonzepten und Schulleistungsentwicklung in verschiedenen Lernumgebungen (mathematica didactica, 2006)
Motivational variables are considered as meaningful individual dispositions for learning processes. On the basis of empirical findings concerning motivation, interest and self concepts in mathematics of grade 8 students, we focus on interactions between different motivation-related variables. Results from a cluster-analysis of the quantitative data gainedin a field study indicate that different motivational profiles might play particular roles for the development of motivational variables and proof competence, which seem not to be independent from specific learning environments.